Using computed tomography to evaluate proper chest compression depth for cardiopulmonary resuscitation in Thai population: A retrospective cross-sectional study - Atiksawedparit, Pongsakorn; Sathapornthanasin, Thanaporn; Chalermdamrichai, Phanorn; Sanguanwit, Pitsucha; Saksobhavivat, Nitima; Saelee, Ratchanee; Phattharapornjaroen, Phatthranit (PloS one, 2023)
The effectiveness of cardiopulmonary resuscitation is determined by appropriate chest compression depth and rate. The American Heart Association recommended CC depth at 5-6 cm to indicate proper cardiac output during cardiac arrest. However, many studies showed the differences in the body builds between Caucasians and Asians. Therefore, this study aimed to determine heart compression fraction (HCF) in the Thai population by using contrast-enhanced computed tomography (CT) scan of the chest and a mathematical model. Consecutive contrast-enhanced CT scans of the chest performed at Ramathibodi Hospital were retrospectively reviewed from January to March 2018 by two independent radiologists. Patients' characteristics, including gender, age, weight, height, and pre-existing diseases, were recorded, and the chest parameters were measured from a CT scan. The heart compression fraction (HCF) was subsequently calculated. Of 306 subjects, there were 139 (45.4%) males, 148 (47.4%) lung diseases and 10 (3.3%) heart diseases. Mean age and BMI were 60.4 years old and 23.8 kg/m2, respectively. Chest diameter, heart diameter, and non-cardiac soft tissue were significantly smaller in females compared to males. Mean (SD) HCF proportional with 50 mm and 60 mm depth were 38.3% (13.3%) and 50% (14.3%), respectively. There were significant differences of HCF proportional by 50 mm and 60 mm depth between men and women (33.2% vs 42.6% and 44% vs 54.9%, respectively (P<0.001)). In addition, a decrease in HCF was significantly observed among higher BMI groups. The CT scan and mathematical model showed that 38% and 50% HCF proportions were generated by 50 mm and 60 mm CC depth. HCF proportions were significantly different between genders and among BMI groups. The recommended depth of 5-6 cm is likely to provide sufficient CC depth in the population of Thailand.